Morphometric Analysis of Calcaneal Angles in Igbos of South East of Nigeria and Its Clinical Implication: A plain X-ray study - Katchy, Amechi Uchenna; Njeze, Ngozi Rosemary; Okoroafor, David (Nigerian Journal of Orthopaedics and Trauma, 2018)
Introduction: The calcaneum is repeatedly subjected to static and dynamic stresses especially in the weight‑bearing positions during walking, working or running and this is reflected in the trabecular pattern within the calcaneus. There are six radiological angles associated with this bone notably the Böhler (tuber joint) angle (BA) and Gissane’s angle (GA), and they vary in different ethnic population. Aim: This is to determine the calcaneal angles among the ethnic Igbos of South Eastern Nigeria, determine the relationships between these angles, determine any correlation with gender and age, compare the values of the BA and GA to that of other populations and discuss the clinical implications of the determined values. Methodology: A 5‑year review of all lateral views of X‑rays of the foot and ankle done at Federal Teaching Hospitals, Abakaliki, Nigeria, from 1st January 2012 to 31st December 2016, was done. Drawing and mathematical sets were used to measure the six radiological angles on the lateral views of plain X‑ray films of the ankle and subjected them to descriptive and inferential statistics. Results: There were 120 patients, 65 males and 55 females. The calcaneal angles among the ethnic Igbos of South Eastern Nigeria showed the following: BA: 32.58 ± 4.98, GA: 121.22 ± 6.11, calcaneal compression angle: 30.00 ± 3.01, talocalcaneal angle (TCA): 22.58 ± 5.28, calcaneal pitch angle: 17.35 ± 3.79 and apical angle (AA): 67.24 ± 7.27. There was no relationship between these angles. The TCA and AA showed a correlation with gender and age and other angles did not. There was a statistically significant difference between BA values in this study and that of Ugandan and American populations (P < 0.05). There was a statistically significant difference between the GA values in this study and that of Turkish, New Zealand and Indian populations. Conclusion: These determined values would be a useful tool in the management of patients of Igbo extraction with of the foot pathology.